2011
DOI: 10.3354/ab00330
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental physiological effects of the invasive alga Caulerpa racemosa on the Mediterranean white seabream Diplodus sargus

Abstract: Observational data suggest that the white seabream Diplodus sargus, a sparid fish of economic and ecological relevance in the Mediterranean Sea, has included the invasive green alga Caulerpa racemosa in its diet. Here we adopted a chemoecological approach to study the trophic relationship between the fish and the exotic pest. We demonstrated that the red pigment caulerpin, the most abundant secondary metabolite of C. racemosa, enters food chains and accumulates in the fish tissues. General biological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 65 publications
5
58
4
Order By: Relevance
“…Moreover, in the same studies [50,51] the exposure to the alga was also demonstrated to induce a) alteration of the activity of the Na + -K + -ATPase, which is responsible for the electrochemical gradient across the plasma membrane and it is critical for the osmotic balance of the cell, the resting membrane potential, and the excitable properties of muscle and nerve cells [54][55][56][57][58], b) neurotoxic effects, documented by acetylcholinesterase inhibition, and c) changes in the morphology of gonads. The observed alterations may cause detrimental health status and altered behaviour in the fish, potentially preventing the reproductive success of fish population [51].…”
Section: Biomarkers As Useful Tool For Detecting Subtle Effects Of Bimentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, in the same studies [50,51] the exposure to the alga was also demonstrated to induce a) alteration of the activity of the Na + -K + -ATPase, which is responsible for the electrochemical gradient across the plasma membrane and it is critical for the osmotic balance of the cell, the resting membrane potential, and the excitable properties of muscle and nerve cells [54][55][56][57][58], b) neurotoxic effects, documented by acetylcholinesterase inhibition, and c) changes in the morphology of gonads. The observed alterations may cause detrimental health status and altered behaviour in the fish, potentially preventing the reproductive success of fish population [51].…”
Section: Biomarkers As Useful Tool For Detecting Subtle Effects Of Bimentioning
confidence: 84%
“…In two recent studies [50,51] carried out along the Apulian coasts (Northern Ionian Sea, SE Italy) the authors found that C. racemosa changes foraging habit of the native white seabream, Diplodus sargus. In invaded areas, a high frequency of occurrence of C. racemosa in the stomach contents of this omnivorous fish was found in parallel with a significant accumulation of caulerpin, one of the main secondary metabolites of C. racemosa, in fish tissues.…”
Section: Biomarkers As Useful Tool For Detecting Subtle Effects Of Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Although both multiple-use MPAs and no-take reserves could indirectly mitigate human impacts by increasing the resilience of protected systems (Bellwood et al 2004, Hughes et al 2005, they cannot directly cope with many external stressors, such as terrestrial pollution, spread of pathogens, climate change and marine invasive species (Halpern et al 2008, Mora & Sale 2011, Terlizzi et al 2011 and they are most useful when embedded into broader, multisector management plans (Fraschetti et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since no valid eradication method has been published on this species, C. racemosa has been continuing its invasion in the Mediterranean Sea. Its effects on the sublittoral ecosystem of the Mediterranean Sea have been mentioned in many reports (Terlizzi et al, 2011;Katsanevakis et al, 2011;Box et al, 2010;Deudero et al, 2010;Klein&Verlaque, 2008). Caulerpa prolifera (Forsskål) J.V.…”
Section: Introductionmentioning
confidence: 99%